Peningkatan Kemampuan Menghafal Asmaul Husna Melalui Metode Gerakan di TPA - Sofyan Harahap; Eka Saputri; Karni Karni; Imam Handoyo; Annisa Meilia Utami; Mutiara Dewi; Muhammad Fillah (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2024)
Memorizing Asmaul Husna through the movement method at one of the Dadapan Village TPAs aims to increase the memorization of Asmaul Husna for children at the Dadapan Village TPA. The movement method is used to help the memorization process because this method is very creative and can be used as a support for Asmaul Husna learning. The results of memorizing Asmaul Husna show that there is active participation from both children. This memorization program is also fully supported by the TPA and parents. Asmaul Husna's learning using movement and singing methods was successfully implemented in TPA and was successful in improving children's memorization abilities.